Penguatan pendidikan karakter model social problem solving bagi siswa sekolah dasar - Wahjusaputri, Sintha; Bunyamin, Bunyamin; Nastiti, Tashia Indah (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2019)
The purpose of community service activities to know how to strengthen the character education model for elementary school students of Muhammadiyah 11 Tanjung Lengkong Jakarta and its application. Research and Development (R &D) used for the research method, there are consist of four step: (1) the preliminary step is the firs activity and collecting student information; (2) The planning stage of character education model for students as the development of initial product form; (3) Trial, evaluation and revision phases, and (4) Implementation step of character education. To measure the successful implementation of character education using the Delphi technique. Based on expert judgment, the strengthening of character education model of SD Muhammadiyah 11 Tanjung Lengkong Jakarta can be measured using the Social Problem Solving model. The result of the strengthening of character education model was found on the social skills enhancement of elementary school students of Muhammadiyah 11 Tanjung Lengkong with an average score of 3.75. Therefore the use of Model Social Problem Solving is worth using.